Introducing artificial intelligence through classroom debates: a student-centric approach - Zulkarnain, Nur Zareen; Mansor, Majdina (Springer, 2024)
Learning artificial intelligence (AI) demands students to grasp under- lying concepts and cultivate critical reasoning for real-world problem-solving. However, conventional unidirectional pedagogies often struggle to foster these aptitudes. This paper introduces an innovative approach, employing classroom debates as an initial-week activity to familiarize students with AI concepts. Divided into supporting and opposing teams, students are tasked with finding points sub- stantiating their positions. Subsequently, a few students will be selected to engage in the debate, while the remaining act as citizen juries, responsible for voting on the winning team. By fostering an open, explorative atmosphere, this approach allows educators to gauge prior knowledge, nurture critical thinking, and ensure engaging sessions. The effectiveness of this approach was evaluated through a survey capturing student perceptions. The results revealed a positive response, with mean scores for each question ranging from 5.24 to 6.21. Nonetheless, the significant standard deviation across questions underscores varying opinions and view-points. Notably, the question with the highest mean and lowest standard devi- ation pertains to students’ preference for learning through this activity compared to traditional methods.